2011
DOI: 10.4142/jvs.2011.12.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factors and genetic variability of uropathogenicEscherichia coliisolated from dogs and cats in Italy

Abstract: In this study, the association between virulence genotypes and phylogenetic groups among Escherichia (E.) coli isolates obtained from pet dogs and cats with cystitis was detected, and fingerprinting methods were used to explore the relationship among strains. Forty uropathogenic E. coli (UPEC) isolated from dogs (n = 30) and cats (n = 10) in Italy were analysed by polymerase chain reaction (PCR) for the presence of virulence factors and their classification into phylogenetic groups. The same strains were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
3
13
0
1
Order By: Relevance
“…Also similar to previous studies [9], B2 was the most common class among isolates that expressed UVFs. The more hich contained fewer UVFs than group B2.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Also similar to previous studies [9], B2 was the most common class among isolates that expressed UVFs. The more hich contained fewer UVFs than group B2.…”
Section: Resultssupporting
confidence: 73%
“…Another study found that while B2 was less prevalent among resistant organisms compared to susceptible organisms, it was still the most dominant class in resistant organisms [14]. A third study also found B2 to be the most common class among UPEC but did not differentiate susceptible versus resistant organisms [9]. To the authors' knowledge, the correlation between the presence of UVFs, phylogenetic class, and antimicrobial resistance in E. coli isolates from dogs with UTIs has not previously been investigated.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ibenyassine et al (2006) used the same technique and evaluated the similarity of isolates from plants infected by irrigation water. Other authors have used ERIC-PCR to compare E. coli isolates from humans and animals (Leung et al, 2004;Sabate et al, 2008;Tramuta et al, 2011;De la Fé Rodriguez et al, 2012). Moreover, Casarez, Pillai, Di Giovanni, (2007), Duan et al (2009), andWan et al (2011) showed that ERIC-PCR could discriminate E. coli from water and environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…O marcador fimH, também foi o mais encontrado em trabalhos realizados em pacientes com ITU na Suécia (96 %), Inglaterra (97 %) e China (80 %) (NORINDER et al, 2012, MLADIN et al, 2009, GIBREEL et al, 2011, ABDALLAH et al, 2011. Até mesmo pacientes com disfunção do trato urinário, no caso 51 bexiga neurogênica, apresentaram uma alta prevalência desse marcador (80 %) (TRAMUTA et al, 2011). O segundo marcador de virulência mais encontrado em nosso trabalho foi (pap) para a fimbria P (53,33%), seguido pelo marcador genético para a fimbria do tipo S (sfa) (32,22%), fenótipo de hemólise α (28,89%), marcador genético para Hemolisina-α (hly) (21,11%) e marcador genético da toxina Pic (10%) (Gráfico 12, Figura 7, Figura 8, Figura 9, Figura 10, Figura 11).…”
Section: Quadro Clínico Dos Pacientes Com Ituunclassified